Design and rationale of the HANSE Study: a holistic German lung cancer screening trial using low-dose computed tomography : chest = Design und Rationale der HANSE-Studie : eine ganzheitliche deutsche Lungenkrebs-Früherkennungs-Studie unter Verwendung von Niedrigdosis-Computertomografie - Vogel-Claussen, Jens; Lasch, Florian; Bollmann, Benjamin-Alexander; May, Katharina; Kuhlmann, Alexander; Schmid-Bindert, Gerald; Kaaks, Rudolf; Barkhausen, Jörg Johannes; Bohnet-Joschko, Sabine; Reck, Martin (RöFo, 2022)
Despite the high prevalence and mortality of lung cancer and proven effectiveness of low-dose computed tomography (LDCT) to reduce mortality, Germany still lacks a national screening program. The German Institute for Quality and Efficiency in Health Care (IQWiG) and the Federal Office for Radiation Protection (BfS) both published positive scientific evaluations recommending a quality-controlled national screening program. IQWiG underlined the importance of a clear risk definition, integrated smoking cessation programs, and quality assurance, highlighting the necessity of procedural optimization. In the HANSE study, former and current smokers aged 55-79 years are assessed for their lung cancer risk by the NELSON and PLCO M2012 risk scores. 5000 high-risk participants, defined as PLCO M2012 6-year risk ≥ 1.58 % or fulfilling NELSON risk inclusion criteria, will be screened by LDCT at baseline and after 12 months. Lung nodules are analyzed by a modified Lung-RADS 1.1 score of the HANSE study, and values of emphysema and coronary calcium are determined and randomly reported to the participants. 7100 low-risk participants serve as a control. All patients are followed-up for up to 10 years. The sensitivity and specificity of the two risk assessments and LDCT screening, effects of the randomized LDCT reporting, efficiency of lung nodule management, and several other factors are assessed to analyze the success and quality of the holistic screening program. The HANSE study is designed as a holistic lung cancer screening study in northern Germany to answer pressing questions for a successful implementation of an effective German lung cancer screening program.
Gesehen am 27.06.2023